Measurement of the [Formula: see text] production cross section in the tau + jets channel using the ATLAS detector - ATLAS Collaboration; Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; et al. (The European physical journal. C, Particles and fields, 2013)
A measurement of the top quark pair production cross section in the final state with a hadronically decaying tau lepton and jets is presented. The analysis is based on proton-proton collision data recorded by the ATLAS experiment at the LHC, with a centre-of-mass energy of 7 TeV. The data sample corresponds to an integrated luminosity of 1.67 fb-1. The cross section is measured to be [Formula: see text] and is in agreement with other measurements and with the Standard Model prediction.